Semiotic Analysis of Surau dan Silek Movie Posters - Pratiwi, Anne; Amri, Ulil; Suandari, Fitri (Puitika, 2024)
Movie posters are means of media promotion for an upcoming movie to persuade the moviegoers attending the cinema or to spread awareness of the near future release. In general, movie posters are embedded with initial information about the movie, i.e., the title, a short tagline, actors and actresses, production house, producers, and the team beyond its production. The information in a movie poster can be conveyed in various signs which are classified into two: linguistic and non-linguistic signs. This research aims to identify linguistic and non-linguistic signs and to analyze denotative and connotative meaning the signs found on the poster of Surau dan Silek, the debut full-length movie by Arief Malinmudo, by applying Barthes’ order of signification theory. The data are in the form of symbols found on the selected poster. This research is descriptive qualitative research. The result shows that the symbols convey numerous messages in explicit and implicitways, including information about the premise of the movie, cultural values and cultural references embedded to the story, its production detail, the actors and actresses, the characters, settings, and the moral lesson from the movie.